Health Self-management Among Older Prisoners: Current Understandings and Directions for Policy, Practice, and Research. Issue 7 (16th November 2016) - Ruggiano, Nicole; Lukic, Andreja; Blowers, Anita; Doerner, Jill
ABSTRACT: The population of aging prisoners has increased significantly over the past several decades, resulting in concerns about the criminal justice system's ability to address the needs of prisoners and parolees with chronic health conditions. This is troubling, given the health disparities among incarcerated populations. Health self-management has become a strategy within the community-based health care industry to improve health services and outcomes while reducing health care costs for nonincarcerated individuals with chronic conditions. However, to date little research has focused on the practice or promotion of health self-management among current and former incarcerated populations. This article highlights current understandings about chronic health self-management among older prisoners and parolees, with an emphasis on the potential benefits and current challenges in promoting their health self-management practices. Finally, specific recommendations are made for promoting health self-management for these populations through social work practice, policy advocacy, and research to achieve goals in improving health outcomes and reducing healthcare costs.